Odpowiedź :
a)
[tex]x^2-2x+5=0\\\Delta=b^2-4ac=4-20=-16\\x\not\in\mathbb{R}[/tex]
b)
[tex]-2x^2+3x+5=0\\\Delta=b^2-4ac=9+40=49\\x_1=\cfrac{-b-\sqrt\Delta}{2a}=\cfrac{-3-\sqrt{49}}{-4}=\cfrac{-3-7}{-4}=2.5\\x_2=\cfrac{-b+\sqrt\Delta}{2a}=\cfrac{-3+\sqrt{49}}{-4}=\cfrac{-3+7}{-4}=-1[/tex]
c)
[tex]x^2+4=0\\\Delta=b^2-4ac=0-16=-16\\x\not\in\mathbb{R}[/tex]
d)
[tex]x^2+x-1=0\\\Delta=b^2-4ac=1+4=5\\x_1=\cfrac{-b-\sqrt\Delta}{2a}=\cfrac{-1-\sqrt{5}}{2}\\x_2=\cfrac{-b+\sqrt\Delta}{2a}=\cfrac{-1+\sqrt{5}}{2}[/tex]
e)
[tex]-x^2-2x+3=0\\\Delta=b^2-4ac=4+12=16\\x_1=\cfrac{-b-\sqrt\Delta}{2a}=\cfrac{2-\sqrt{16}}{-2}=\cfrac{2-4}{-2}=1\\x_2=\cfrac{-b+\sqrt\Delta}{2a}=\cfrac{2+\sqrt{16}}{-2}=\cfrac{2+4}{-2}=-3[/tex]
f)
[tex]2x^2-4x+11=0\\\Delta=b^2-4ac=16-88=-72\\x\not\in\mathbb{R}[/tex]
Wykres w załączniku